When is a Whale Sanctuary Not a Whale Sanctuary? Japanese Whaling in Australian Antarctic Maritime Zones - Mossop, Joanna (Victoria University of Wellington Law Review, 2005)
This article concerns the case of Humane Society International v Kyodo Senpaku Kaisha Ltd, in which the Humane Society, a non-governmental organisation, attempted to sue a Japanese company conducting whaling in the Southern Ocean in an area claimed as an exclusive economic zone by Australia. The Humane Society failed to convince the Federal Court to allow it to serve proceedings on the Japanese company outside Australia, after the judge agreed with the arguments provided by the Australian Attorney-General. These submissions included the possibility of an embarrassing international incident that could arise if a Japanese company were to be served with proceedings enforcing a law that Japan considers to be inconsistent with the freedom of navigation on the high seas. Underpinning the whole case was the issue of sovereignty over Antarctica, which Australia and other countries have disputed for many decades. The author evaluates Australia’s claim to an exclusive economic zone around its Antarctic territorial claim, and its use of the Environment Protection and Biodiversity Conservation Act 1999 to declare a whale sanctuary in that part of the world. The author suggests that it might be possible for the Australian courts to read the whale sanctuary legislation in line with international law, potentially relying on the New Zealand Sellers case, to exclude overseas companies from the effects of the legislation. However, the author concludes it would not be desirable for the Australian Government to rely on such a possibility to avoid potential international repercussions from its domestic legislation.